2017
DOI: 10.5539/jas.v9n11p99
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Factors Influencing Market Participation of Smallholder Bean Farmers in Nyanza District of Southern Province, Rwanda

Abstract: Rwanda remains trading very low volume of beans inside the country and across borders thereby becoming unable to meet national and international demands. This is exacerbated by low market participation of bean growers. This study assessed factors that influence market participation and extent of participation among bean growers in Nyanza district. Probit model was used to analyze the factors influencing market participation among bean growers while the extent of market participation was analyzed using Tobit mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
19
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 11 publications
9
19
1
Order By: Relevance
“…Indeed, several studies have shown that women are more involved in the common bean trade [ 45 , 66 , 67 ]. The significant increase of commercial use of common beans with increasing informant age was contrary to the results of Mbitsemunda and Karangwa [ 68 ] which found that age negatively and significantly influenced common bean commercial use. Similarly, Birachi et al [ 69 ] indicate that younger farmers are more likely marketing beans than older farmers.…”
Section: Discussioncontrasting
confidence: 98%
“…Indeed, several studies have shown that women are more involved in the common bean trade [ 45 , 66 , 67 ]. The significant increase of commercial use of common beans with increasing informant age was contrary to the results of Mbitsemunda and Karangwa [ 68 ] which found that age negatively and significantly influenced common bean commercial use. Similarly, Birachi et al [ 69 ] indicate that younger farmers are more likely marketing beans than older farmers.…”
Section: Discussioncontrasting
confidence: 98%
“…The farmer's age was found to be significant, though negatively correlated to market participation. This finding is supported by other studies such as [34][35], where significant negative relationships between age and market participation were reported, and contrasts with the view of [36], which considers age as an enabler of market participation. These sources allude to risk aversion and conservative attitudes among older farmers, against the market-enthusiasm exhibited by younger farmers, to elucidate the negative correlation between age and market participation among some farmers.…”
Section: Effect Of Identified Variables On Market Participationsupporting
confidence: 79%
“…This position is also supported by [8], where the explanatory variables jointly influenced the extent of market commercialization. Other relevant studies where combinations of variables were identified as influencing market participation decisions, either positively or negatively, among surveyed smallholder farmers include [23,35,40] and also in [56].…”
Section: Effect Of Identified Variables On Market Participationmentioning
confidence: 99%
“…The farmer's age was found to be significant, but negatively correlated to market participation. This finding is supported by other studies such as [46,47], where significant negative relationships between age and market participation were reported, and contrasts with the view [48] that age is an enabler of market participation. These authors allude to risk aversion and conservative attitudes among older farmers versus the market-enthusiasm exhibited by younger farmers to elucidate the negative correlation between age and market participation among some farmers.…”
Section: Effect Of Identified Variables On Market Participationsupporting
confidence: 76%